Joint- and load-specific asymmetries during three lower extremity resistance training exercises - Haischer, M. H.; Ahn, N.; Kim, H.; Jacobson, E.; Kipp, K. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was characterize the consistency of limb symmetries at the knee and hip in the front squat, hexagonal barbell deadlift, and Romanian deadlift across three loads (40%, 60%, 80% of front squat one-repetition maximum). Eight female collegiate soccer players performed three repetitions at each aforementioned load and for each exercise while motion capture and ground reaction force data were recorded. Bilateral net joint moments were calculated and used to quantify joint-specific limb symmetry indices (LSI) for each exercise and loading condition. Correlation analyses revealed similarity in LSI at the knee and hip within all exercises and between the front squat and hexagonal barbell deadlift. At the joint level, greater biomechanical similarity between tasks seems to result in greater consistency of interlimb asymmetries.